1998
DOI: 10.1097/00004728-199803000-00021
|View full text |Cite
|
Sign up to set email alerts
|

MR Evaluation of Human Anterior Cruciate Ligament Autograft on Oblique Axial Imaging

Abstract: We conclude that high signal intensity can be seen within stable ACL grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 13 publications
0
34
0
1
Order By: Relevance
“…⁎⁎ SIR is significantly higher at 6 months postoperatively than at 3 or 12 months postoperatively (p b 0.0001). months postoperatively [26], and was attributable to proliferating hypervascular tissue embracing the graft [27,28]. In the present study, mean SIR was compared between groups at 12 months postoperatively, because several human studies have proposed that at least 12 months are needed to complete graft maturation [29][30][31][32] and allow patients to resume strenuous sports activities.…”
Section: Discussionmentioning
confidence: 96%
“…⁎⁎ SIR is significantly higher at 6 months postoperatively than at 3 or 12 months postoperatively (p b 0.0001). months postoperatively [26], and was attributable to proliferating hypervascular tissue embracing the graft [27,28]. In the present study, mean SIR was compared between groups at 12 months postoperatively, because several human studies have proposed that at least 12 months are needed to complete graft maturation [29][30][31][32] and allow patients to resume strenuous sports activities.…”
Section: Discussionmentioning
confidence: 96%
“…It has been demonstrated that the ACL may be imaged effectively in planes that are based on the natural course of the ligament, and it is likely that this will also facilitate visualization of the individual AM and PL bundles [3,9,13]. Two such planes of view are the para-coronal plane and the oblique-sagittal plane (Fig.…”
Section: Inter-observer Evaluationmentioning
confidence: 99%
“…Reconstruction of the ACL was carried out under arthroscopy using a combination of a double-looped autogenous semitendinosus-gracilis tendon graft and a LeedsKeio artificial ligament graft simultaneously. 18 No surgical insult was inflicted to the quadriceps femoris muscle or extensor mechanism. The mean interval between the injury and the ACL reconstruction was 7.5 months within a range of 2 to 26 months.…”
Section: Subjectsmentioning
confidence: 99%